1997
DOI: 10.1073/pnas.94.16.8830
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate receptor-mediated toxicity in optic nerve oligodendrocytes

Abstract: In cultured oligodendrocytes isolated from perinatal rat optic nerves, we have analyzed the expression of ionotropic glutamate receptor subunits as well as the effect of the activation of these receptors on oligodendrocyte viability. Reverse transcription-PCR, in combination with immunocytochemistry, demonstrated that most oligodendrocytes differentiated in vitro express the ␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor subunits GluR3 and GluR4 and the kainate receptor subunits GluR6, Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
268
2
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 334 publications
(288 citation statements)
references
References 27 publications
16
268
2
2
Order By: Relevance
“…Interestingly, these authors also found that MK801 reduced the size of hemorrhage in grey matters and protected the spinal cord white matter, though NMDA receptors probably do not present on the vessels of neural tissue 77,78 and CNS white matter. 79,80 However, our results are consistent with some investigations on the role of ionotropic glutamate receptor antagonists. For example, local injection of the non-NMDA receptor antagonist, 6,7-dinitro-quinoxaline-2,3-dione (DNQX), into the ventrobasal thalamic nucleus, resulted in a decrease in amplitude and an increase in latency of cortical SEPs.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, these authors also found that MK801 reduced the size of hemorrhage in grey matters and protected the spinal cord white matter, though NMDA receptors probably do not present on the vessels of neural tissue 77,78 and CNS white matter. 79,80 However, our results are consistent with some investigations on the role of ionotropic glutamate receptor antagonists. For example, local injection of the non-NMDA receptor antagonist, 6,7-dinitro-quinoxaline-2,3-dione (DNQX), into the ventrobasal thalamic nucleus, resulted in a decrease in amplitude and an increase in latency of cortical SEPs.…”
Section: Discussionsupporting
confidence: 92%
“…However, we failed to detected X-gal staining or immunoreactivity in CNPase-positive cells in myelinated tracts of the corpus callosum, cerebellum or other areas, and we are not aware of in situ hybridization studies reporting NR2C expression in oligodendrocytes. The lack of NR2C-nβ-gal expression in oligodendrocytes is consistent with earlier studies that failed to detect NMDAR expression in the optic nerve (Matute et al, 1997) and cultured oligodendrocytes (Patneau et al, 1994). However, electrophysiology is a very sensitive method and we cannot exclude the possibility that NR2C expression is either transient and can be activated by anoxia, or is below the detection levels in these cells.…”
Section: Expression Of the Nr2c In Non-neuronal Cellssupporting
confidence: 74%
“…Oligodendrocytes are sensitive to excitotoxic insults mediated by overactivation of their AMPA/kainate ionotropic glutamate receptors (Yoshioka et al, 1996;Matute et al, 1997;McDonald et al, 1998;Sanchez-Gomez and Matute, 1999). Excitotoxicity in oligodendrocytes, as well as in neurons, is completely dependent on Ca 21 entry through the ionotropic glutamate receptor (Choi, 1995;Alberdi et al, 2002;Krieger and Duchen, 2002).…”
Section: Introductionmentioning
confidence: 99%